High-Risk Interactions for Transmission of CRE to Health Worker Gloves or Gown: A Multicenter Cohort Study. (October 2020) - Calfee, David; Miller, Loren; Nguyen, Minh-Hong; Pineles, Lisa; Magder, Laurence; Johnson, J. Kristie; Morgan, Daniel; Harris, Anthony
Abstract : Background: Carbapenem-resistant Enterobacteriaceae (CRE) are a serious threat to public health due to high associated morbidity and mortality. Healthcare personnel (HCP) gloves and gowns are frequently contaminated with antibiotic-resistant bacteria, including CRE. We aimed to identify patients more likely to transmit CRE to HCP gloves or gowns and HCP types and interactions more likely to lead to glove or gown contamination. Methods: Between January 2016 and August 2018, patients with a clinical or surveillance culture positive for CRE in the preceding 7 days were enrolled at 5 hospitals in California, Maryland, New York, and Pennsylvania. Ten HCP–patient interactions were observed for each patient and were recorded by research staff. Following patient care, but prior to doffing, the gloves and gown of each HCP were sampled for the presence of CRE. Results: We enrolled 313 CRE-colonized patients, and we observed 3, 070 HCP interactions. CRE was transmitted to HCP gloves in 242 of 3, 070 observations (7.9%) and to gowns in 132 of 3, 070 observations (4.3%). Transmission to either gloves or gown occurred in 308 of 3, 070 interactions observed (10%). The most frequently identified organism was Klebsiella pneumoniae (n = 171, 53.2%), followed by Enterobacter cloacae (n = 36, 11.2%), and Escherichia coli (n = 33, 10.3%). Patients in the intensive care unit (n = 177, 56.5%) were more likely to transmit CRE to HCP gloves or gown (OR, 1.65; 95% CI, 1.03–2.64) compared to those not in an ICU and adjusted for HCP type. The odds of CRE transmission increased with the number of different items touched near the patient (OR, 1.32; 95% CI, 1.21–1.44) and with the number of different items touched in the environment (OR, 1.13; 95% CI, 1.06–1.21). Respiratory therapists had the highest rates of transmission to gloves and gown (OR, 3.79; 95% CI, 1.61–8.94), followed by physical therapists and occupational therapists (OR, 2.82; 95% CI, 1.01–8.32) when compared to HCP in the "other" category. Manipulating the rectal tube (OR, 3.03; 95% CI, 1.53–6.04), providing wound care (OR, 2.81; 95% CI, 1.73–4.59), and touching the endotracheal tube (OR, 2.79; 95% CI, 1.86–4.19) were the interactions most strongly associated with CRE transmission compared to not touching these items and adjusted for HCP type. Conclusions: Transmission of CRE to HCP gloves and gowns occurs frequently. We identified interactions and HCP types that were particularly high risk for transmission. Infection control programs may wish to target infection prevention resources and education toward these high-risk professions and interactions. Funding: This work was supported by the CDC Prevention Epicenter Program (U43CK000450-01) and the NIH National Institute of Allergy and Infectious Diseases (R01 AI121146-01). Disclosures: None